Mental Health Burden of the COVID-19 Pandemic in Healthcare Workers in Four Latin American Countries - Roberto Ariel Abeldaño Zuñiga PhD; Hugo Juanillo-Maluenda PhD; María Alejandra Sánchez-Bandala PhD; Graciela Verónica Burgos MSc; Silvina Andrea Müller BSc; Jorge Rafael Rodríguez López MSc (SAGE Publishing, 2021)
The aim of the study was to assess the mental health burden of the COVID-19 pandemic in healthcare workers in four Latin American countries in 2020. An online survey was carried out with 1721 participants from Argentina, Chile, Colombia and Mexico in 2020. A non-probabilistic convenience sampling method was used to recruit voluntary participants. Post-traumatic stress symptoms were assessed with the SPRINT-E scale, Perceived Discrimination was assessed with a Spanish version of the scale developed by Molero, and anxiety toward death was assessed with the Spanish version of the Templer scale. All instruments were assessed for internal consistency. The overall frequency of post-traumatic stress symptoms was 23.9%. The frequency by countries was 26.4% in Argentina, 29.8% in Chile, 19.9 in Colombia, and 23.8% in Mexico. Post-traumatic stress symptoms were associated with individual subtle discrimination, anxiety toward the death of the elderly, lack of Personal Protective Equipment, and exposition to the death. The COVID-19 pandemic has imposed a mental health burden on health workers in the countries included in the study, not only due to the implications of the disease in the face of exposure to death, but also due to institutional conditions and in which they carry out their work.